Analysis Of Financial Statement Ratio At Pt Bank Bri Syariah Tbk According To Islamic Perspective - Fatma, Aprillia Dwi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research was conducted to determine the ratio analysis of financial statements at PT Bank BRI Syariah Tbk, namely through profitability ratios. This research uses ratio analysis methodology, which is to analyze using comparisons of quantitative data shown in the balance sheet and profit and loss report. The results of the analysis of the discussion in this research showed that the Net Profit Margin in 2017 was 5.67% (five point sixty seven), in 2018 it was 5.39% (five point thirty nine), and in 2019 it was 3.21% (three point twenty one). Return on assets in 2017 was 0.32% (zero point thirty two), in 2018 it was 0.28% (zero point twenty eight), and in 2019 it was 0.17% (zero point seventeen). Return On Equity in 2017 was 3.88% (three point eighty eight), in 2018 was 2.12% (two point twelve), and in 2019 was 1.45% (one point forty five). The development of the level of profitability at PT Bank BRI Syariah Tbk in 2017 - 2019 has decreased every year because there is a decrease in accordance with the amount of company revenue. The profitability ratio of financial statements at PT Bank BRI Syariah Tbk is in accordance with an Islamic perspective.